BAIT-FISH AND TUNA CATCHES AT MINICOY ISLAND (LAKSHADWEEP) IN RELATION TO LUNAR CYCLE DURING 1983-84 SEASON - Mohan, Madan; Kunhikoya, K K (Indian Journal of Fisheries, 2011)
The catches of bait-fish and tuna in relation to moon phases during 1983-84 pole-and-line tuna-fishing season is discussed. Bait-fish and tuna catches for the season as a whole were relatively high during new-moon phase and low ’during the last quarter of the moon. Tuna catches per kg of bait fish were high during the last quarter of moon and low during newmoon phase. Efforts in both bait fishing and tuna fishing and catehes-per-unit-of-effort of bait fishes and tuna were highest during newmoon phase, then decreased gradually and was lowest in the last quarters.